Advancing knowledge on the biogeography of arbuscular mycorrhizal fungi to support Sustainable Development Goal 15: Life on Land - Stewart, Justin D; Corrales, Adriana; Canteiro, Cátia; Qin, Clara; Gupta, Manju M; Otgonsuren, Burenjargal; Peña-Venegas, Clara P; Van Nuland, Michael E; Kohout, Petr; Větrovský, Tomáš; Kokkoris, Vasilis; Manley, Bethan F (FEMS microbiology letters, 2025)
Arbuscular mycorrhizal (AM) fungi are fundamental to planetary health, enhancing plant nutrient uptake, stabilizing soils, and supporting biodiversity. Due to their prevalence and ecological importance, AM fungi are critical to achieving the environmental targets within the United Nations (UN) Sustainability Development Goals (SDGs) framework, including SDG 15: Life on Land. Despite these fungi engaging in the most widespread and ancient plant-microbe symbiosis, many fundamental aspects of the biogeography of AM fungi remain poorly resolved. This limits our ability to understand and document these fungal species' contributions to preserving terrestrial life on Earth. Using the largest global dataset of AM fungal eDNA sequences, we highlight that > 70% of ecoregions have no available data generated from soil using AM fungal specific metabarcoding. Drawing attention to these severe data gaps can optimize future sampling efforts in key habitats. Filling these gaps and developing a more complete picture on the biogeographic distributions of AM fungal species will help to clarify their contributions to environmental targets.
Keywords: Plants; conservation; Phylogeography; Ecosystem; ekosystém; fylogeografie; ecoregion; Sustainable Development; symbióza; Symbiosis; arbuscular mycorrhizal fungi; trvale udržitelný rozvoj; biodiverzita; Mycorrhizae; Life on Land; United Nations; půdní mikrobiologie; Sustainable Development Goals; Organizace spojených národů; mykorhiza; biodiversity; rostliny; Soil Microbiology; Biodiversity